Activating Autophagy Enhanced the Antitumor Effect of Antibody Drug Conjugates Rituximab-Monomethyl Auristatin E - Wang, Yichen; Zhang, Xuyao; Fan, Jiajun; Chen, Wei; Luan, Jingyun; Nan, Yanyang; Wang, Shaofei; Chen, Qicheng; Zhang, Yujie; Wu, Youling; Ju, Dianwen (Frontiers in Immunology, 2018)
Antibody drug conjugate (ADC) showed potent therapeutic efficacy in several types of cancers. The role of autophagy in anti-tumor effects of ADC remains unclear. In this study, a novel ADC, Rituximab-monomethyl auristatin E (MMAE) with a Val-Cit cleavable linker, was designed to investigate its therapeutic efficacy against Non-Hodgkin Lymphoma (NHL) as well as the underlying mechanisms. Our results showed that Rituximab-MMAE elicited caspase-3-dependent apoptosis in NHL cells and exhibited potent therapeutic efficacy in vivo. Autophagy, which was characterized by up-regulated LC3-II expression, and formation and accumulation of autophagosomes, was triggered during the ADC treatment. Meanwhile, inactivation of Akt/mTOR pathway was shown to be involved in the autophagy triggered by Rituximab-MMAE, indicating a probable mechanism of ADC-initiated autophagy. Importantly, inhibition of autophagy by chloroquine suppressed the ADC-induced apoptosis, while activating autophagy by rapamycin significantly enhanced the therapeutic effect of Rituximab-MMAE both in vitro and in vivo. Our data elucidated the critical relationship between autophagy and apoptosis in Rituximab-MMAE-based therapy and highlighted the potential approach for NHL therapy by combined administration of ADC and autophagy activation.